Time to recovery from moderate acute malnutrition and its predictors among children aged 6–59 months in Fedis Woreda, East Hararghe Zone, Eastern Ethiopia - Melaku, Berhanu; Gebremichael, Berhe; Negash, Belay; Kitessa, Monas; Kassa, Obsan; Dereje, Jerman; Kefelegn, Reta; Firdisa, Dawit (Frontiers in Nutrition, 2024)
Background Acute malnutrition is a major global public health problem, particularly in low-and middle-income countries. A targeted supplementary feeding program is an approach recommended to address moderate acute malnutrition in food-insecure settings. Preventing and treating moderate acute malnutrition requires identifying factors shown to affect the treatment outcome and duration of stay on treatment. This study aimed to determine the time to recovery from moderate acute malnutrition and its predictors among children aged 6–59 months in Fedis Woreda East Hararghe Zone, Eastern Ethiopia, from January 1 to December 31, 2022. Methods A facility-based retrospective cohort study was conducted on 567 children with moderate acute malnutrition in Fedis Woreda, East Hararghe Zone, eastern Ethiopia. A multi-stage sampling technique was employed, and data was collected using a structured checklist. Data were extracted from randomly selected records after obtaining ethical clearance. Data were cleaned, coded, entered into EpiData 4.6, and analyzed using STATA/SE version 14. Descriptive statistics and analytic analysis schemes, including bivariable and multivariable Cox proportional hazards models, were conducted, and finally, statistical significance was considered at p < 0.05. Results The overall median time to recovery was 16 weeks. The major predicting factors for time to recovery among children aged 6–59 months were admission with a mid-upper arm circumference of 12.1–12.4 centimeters (AHR = 1.02, 95% CI: 1.01–1.19), access to transportation to facilities (AHR = 0.62, 95% CI: 0.36–0.81), children using specialized nutritious foods (RUSF; AHR = 1.96, 95% CI: 1.36–3.11), and children who had diarrhea (AHR = 0.4, 95% CI: 0.31–0.71). Conclusion The study found a median recovery time of 16 weeks for children with targeted supplementary feeding. Significant predictors included admission with a MUAC of 12.1–12.4 centimeters, transportation access, RUSF use, and the presence of diarrhea. These findings highlighted the importance of these factors in determining and improving recovery from moderate-acute malnutrition.